Defisiensi Mikronutrien dan Early Childhood Caries - Athiya Parkesit, Salma; Putriany Agustin, Tri; D. Sjahruddin, Loes (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: Early Childhood Caries (ECC) occurs in children aged 71 months or younger. Untreated ECC and S-ECC adversely affect children's masticatory function, so children tend to choose certain foods. This condition can affect a child's growth, development, and behavior. Micronutrient deficiency is a part of malnutrition, affecting children's growth and development, including tooth development and caries risk. Purpose: To determine the factors involved in the occurrence of ECC and micronutrient deficiencies. Method: This scoping review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and two databases (Pubmed and Wiley Online Library). Result: The result showed that eight journals were found to match the eligibility requirements and were included in this study after an initial search produced a total of 280 journals Conclusion: The risk of ECC is increased in pregnant women and preschool children with vitamin D deficiency. The condition of ECC and S-ECC are the factors causing iron deficiency, vitamin D deficiency, and anemia.